The role of magnetic agents in shaping post-disaster land use - Zavar, Elyse (Land Use Policy, 2016)
Three neighborhoods in Lexington, Kentucky, share a common flood history, including property acquisitions, as a means to mitigate against flooding; yet, the interactions of residents with the buyout landscapes vary significantly among the neighborhoods. Although the same institutions and structural controls implemented flood buyout programs in all three neighborhoods, semi-structured interviews illustrate that differing perspectives, personalities, and neighborhood politics shaped unique identities and land uses for the acquired properties in each neighborhood. Varying levels of resident engagement with the buyout landscape resulted in a range of attitudes towards hazard preparation, management, and mitigation, thus leaving some neighborhoods more resilient to future flooding than others. This study explores key residents, termed magnetic agents, who drove neighborhood civic action and land uses on the open space created through floodplain property acquisition. This research indicates magnetic agents can serve as important partners for local governments and non-governmental organizations (NGOs) in building community-based projects aimed at reducing vulnerability to flood events and instituting high utility land uses on floodplain buyout open space.(C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Agency; Floodplain buyout; Kentucky; Land management; Lexington; Resiliency; United States; dept.egm; flooding; floodplain; hazard management; land management; land use planning; neighborhood; open space